1989
DOI: 10.1002/anr.1780320504
|View full text |Cite
|
Sign up to set email alerts
|

A simplified twenty‐eight–joint quantitative articular index in rheumatoid arthritis

Abstract: We describe a joint index that includes only 28 joints: 10 proximal interphalangeal joints of the fingers, 10 metacarpophalangeal joints, and the wrists, elbows, shoulders, and knees. These joints are evaluated for swelling, tenderness, and limited motion, with the findings scored as abnormal or normal. The articular examination provides the most direct indicator of patient status in rheumatoid arthritis (RA) (1). Joint indices are extensively used in clinical trials (2) and are effectively predictive of long-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
122
0
2

Year Published

1995
1995
2013
2013

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 216 publications
(127 citation statements)
references
References 16 publications
3
122
0
2
Order By: Relevance
“…Prevoo et al found that weighted joint indices did not differ substantially from nonweighted joint indices in the evaluation of disease activity of RA, and recommended use of the 28-joint index based on its simplicity, validity, and reliability (10). Fuchs et al also suggested that weighted scoring system did not actually add substantially to the information derived from a joint count 868 Tanaka et al (22). However, the results obtained with weighted scoring systems of the Thompson-Kirwan and Stewart Articular Index appear to support our results, with the exception of the shoulder joint.…”
Section: Discussionsupporting
confidence: 68%
“…Prevoo et al found that weighted joint indices did not differ substantially from nonweighted joint indices in the evaluation of disease activity of RA, and recommended use of the 28-joint index based on its simplicity, validity, and reliability (10). Fuchs et al also suggested that weighted scoring system did not actually add substantially to the information derived from a joint count 868 Tanaka et al (22). However, the results obtained with weighted scoring systems of the Thompson-Kirwan and Stewart Articular Index appear to support our results, with the exception of the shoulder joint.…”
Section: Discussionsupporting
confidence: 68%
“…This calculation was performed to simulate a standard physician formal 28-joint count, in which only normal/abnormal, rather than a graded score, is recorded (12). Physician and laboratory measures.…”
Section: Methodsmentioning
confidence: 99%
“…Means, medians, and frequencies of RADAI scores were computed for patients with each diagnosis as total scores (range 0 -48) and as the number of involved joint groups (range 0 -16), in order to simulate a physician joint count (in which only normal/abnormal rather than a graded score is recorded) (12). The proportion of patients scoring each specific joint group as painful was also computed for each diagnostic group.…”
Section: Significance and Innovationsmentioning
confidence: 99%
“…'9 Furthermore, only 40-60% of the ingested nitrate appeared in urine,'9 20 which helps to explain why people taking a diet high in nitrate excrete less nitrate in the urine than they ingest. '9 (28) mm/lst h, joint count 20 (6), and early morning stiffness 4 (2) h). Tables 1 and 2 summarise the epidemiological, drug treatment, clinical, and laboratory data of each patient.…”
Section: Introductionmentioning
confidence: 94%